The mechanism of action of calcium antagonists on arrhythmias in early myocardial ischaemia: studies with nifedipine and DHM9. - Curtis, M. J. (1988)
1. Nifedipine and DHM9 (carboxymethyl methyl 1,4-dihydro-2,6-dimethyl-4-(3-nitrophenyl)-3,5-pyridinedicarboxylate) were studied for their effects on arrhythmias resulting from regional myocardial ischaemia in conscious rats, and for their effects on left ventricular developed pressure in vitro. 2. Nifedipine possessed antiarrhythmic activity at a high dose of 10 mg kg-1 i.v., but not at 0.5 or 2 mg kg-1. Ventricular fibrillation (VF), tachycardia (VT), and ventricular premature beats (VPB) were all attenuated to a similar degree; nifedipine did not have a selectivity of action for high frequency arrhythmias. 3. Before coronary occlusion, the three doses of nifedipine reduced arterial blood pressure by a similar magnitude, indicating a similar (maximal) degree of systemic vasodilatation. The reductions in blood pressure were accompanied by reflex tachycardia. Heart rate and blood pressure did not correlate with the incidence or severity of arrhythmias. 4. DHM9 had no influence on arrhythmias, haemodynamic variables or the ECG, even at 20 mg kg-1 i.v. 5. Nifedipine concentration-dependently reduced contractility in perfused paced (5 Hz) rat ventricles in vitro. Raising the concentration of K+ in the perfusion fluid from 3 to 10 mequiv.l-1 increased the potency (-log10 EC50) of nifedipine up to four fold, and caused a significant depression in excitability. 6. DHM9 at up to 3 x 10(-5) M had no significant influence on ventricular contractility in vitro. 7. The results provided indirect evidence in support of the hypothesis that calcium antagonists inhibit ischaemia-induced arrhythmias by virtue of inhibition of the slow inward current (Isi) in the ischaemic ventricular myocardium.